+0  
 
0
116
1
avatar+175 

Can anyone help me with THE LAST PART OF #7 AND #8 thank you:)))

 

 Sep 18, 2019
 #1
avatar+106535 
+2

7) 

 

 f(x)  + f(2)   =  f ( x + 2)

 

 

 

8) 

 

f(a)   = 9(a)^2 + 8

 

f(a + h)  =  9(a + h)^2  + 8    =  9(a^2 + 2ah + h^2) + 8  =  9a^2 + 18ah + 9h^2 + 8

 

f (a + h)  - f(a)            [ 9a^2 + 18ah + h^2 + 8 ] -  [ 9a^2 + 8]          18ah + h^2

___________  =       ______________________________       =   _________   =

                                                  h                                                        h

 

h ( 18a + h)

_________   =         18a  +  h

       h

 

 

 

cool cool cool

 Sep 19, 2019

14 Online Users

avatar
avatar